2017
DOI: 10.1021/acs.jmedchem.6b01897
|View full text |Cite
|
Sign up to set email alerts
|

Kinetin Riboside and Its ProTides Activate the Parkinson’s Disease Associated PTEN-Induced Putative Kinase 1 (PINK1) Independent of Mitochondrial Depolarization

Abstract: Since loss of function mutations of PINK1 lead to early onset Parkinson’s disease, there has been growing interest in the discovery of small molecules that amplify the kinase activity of PINK1. We herein report the design, synthesis, serum stability, and hydrolysis of four kinetin riboside ProTides. These ProTides, along with kinetin riboside, activated PINK1 in cells independent of mitochondrial depolarization. This highlights the potential of modified nucleosides and their phosphate prodrugs as treatments fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 27 publications
7
102
1
2
Order By: Relevance
“…This was judged by parkin Ser65 phosphorylation after treatment with different concentrations of KMP ProTides. Interestingly, the nucleoside kinetin riboside was also able to activate PINK1 in cells to a level comparable to that observed with the most potent KMP ProTide . This suggested that the glycosylation of kinetin into kinetin riboside, rather than the first phosphorylation step, might be the rate‐limiting step of the four bioconversion steps from kinetin to the active KTP.…”
Section: Small‐molecule Pink1 Activatorsmentioning
confidence: 57%
See 3 more Smart Citations
“…This was judged by parkin Ser65 phosphorylation after treatment with different concentrations of KMP ProTides. Interestingly, the nucleoside kinetin riboside was also able to activate PINK1 in cells to a level comparable to that observed with the most potent KMP ProTide . This suggested that the glycosylation of kinetin into kinetin riboside, rather than the first phosphorylation step, might be the rate‐limiting step of the four bioconversion steps from kinetin to the active KTP.…”
Section: Small‐molecule Pink1 Activatorsmentioning
confidence: 57%
“…Encouraged by the success of the ProTide technology in discovering nucleotide‐based therapeutics, we applied this prodrug approach to kinetin riboside monophosphate, KMP . Four KMP ProTides were synthesised with various esters (methyl, isopropyl, tert ‐butyl and benzyl).…”
Section: Small‐molecule Pink1 Activatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,10,11 Given the tremendous importance of phosphor(n)oamidate prodrugs in the antiviral arena and beyond, after the approval of Sofosbuvir and TAF, the application of the ProTide technology has grown dramatically and it has started to show very promising results in other therapeutic areas as well. [12][13][14] While there are several efficient procedures to synthesize phosphoroamidate nucleosides, the phosphonoamidate cognate class especially of acyclic nucleoside phosphonates (ANPs) lacks of such plethora of synthetic methodologies. 15 ANPs play a key role in the treatment of viral infections, and this class of compounds can be regarded as one of the most significant group of drugs in the antiviral field.…”
Section: Introductionmentioning
confidence: 99%